(untitled) (ModaPalavra e-periódico, 2025)
This article is based on bibliographical surveys and a qualitative analysis to reflect on fashion that seeks to break with gender binaries, academic productions about it and the marketing presence of this category in Brazil from a sociological approach that establishes dialogues between the sociology of fashion and gender studies from a post-structuralist and decolonial approach. The objective of this article was to reflect on the challenges of the field of genderless fashion and present the sociological approach as a viable lens for the development of new research, which proliferates the universe of possibilities in this field.